1997
DOI: 10.1001/archpsyc.1997.01830210083010
|View full text |Cite|
|
Sign up to set email alerts
|

Neuroendocrine Response to Fenfluramine Challenge in Boys

Abstract: In young boys, aggressive behavior and social circumstances that are conducive to the development of aggressive behavior are positively correlated with a marker of central serotonergic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(33 citation statements)
references
References 55 publications
0
32
0
Order By: Relevance
“…Likewise, increased prolactin responses to fenfluramine were observed in boys with adverse rearing environment (Pine et al 1997). Since prolactin but not cortisol release is mediated via 5-HT 1A receptors, these findings suggest sensitization of these receptors due to early life stress.…”
Section: Studies In Childrenmentioning
confidence: 70%
“…Likewise, increased prolactin responses to fenfluramine were observed in boys with adverse rearing environment (Pine et al 1997). Since prolactin but not cortisol release is mediated via 5-HT 1A receptors, these findings suggest sensitization of these receptors due to early life stress.…”
Section: Studies In Childrenmentioning
confidence: 70%
“…9 Several lines of evidence have indicated abnormal serotonergic function in children with disruptive behaviour disorders (ADHD, ODD, CD) who display marked problems with hyperactivity, impulsivity, and aggression. [10][11][12][13][14] Animal models of ADHD have also been useful in implicating a role for serotonin in the control of attention, impulsivity, and hyperactivity. Rodents that had poorer performance on a task measuring attention and impulsivity had a greater index of serotonin utilization in the frontal cortex.…”
Section: Using the Transmission Disequilibrium Test (Tdt)mentioning
confidence: 99%
“…Pharmacological challenge studies, which assess 5-HT function by measuring the prolactin response to the 5-HT-release/reuptake inhibitor fenfluramine, have yielded conflicting results. The prolactin-fenfluramine response was found to be significantly enhanced in aggressive boys with ADHD, when compared with non-aggressive ADHD boys [16] ; however, this relationship was only true for younger ADHD boys [17,18] , and was found to be unrelated to aggression in older ADHD boys [19] . It has been suggested that aggressive ADHD children who initially have an enhanced prolactin-fenfluramine response, fail to undergo normal developmental changes in 5-HT function and subsequently might have a blunted response.…”
Section: Introductionmentioning
confidence: 99%